Effect of Roasting on the Chemical Composition and Oxidative Stability of Tomato (Solanum lycopersicum L.) Seed Oil - Zhiya Niu; Zhongyan Zhu; Jing Zhou; Chengjian Xu; Changqing Wei; Wenyu Liu; Zhanxia Liu; Ting Wang; Hang Xiao (Foods, 2024)
In this study, tomato seed (TS) samples were subjected to different roasting conditions (90–170 °C and 10–30 min) to compare their effects on the chemical composition and oxidative stability of tomato seed oil (TSO). Unroasted TS was considered as a control sample. Our results revealed that moderate roasting (130 °C/20 min) can significantly increase the content of linoleic acid (54.01–54.89%), linolenic acid (2.17–2.41%), phytosterols (2789.56–3037.31 mg/kg), squalene (5.06–13.10 mg/kg), total phenols (22.37–22.67 mg GAE/100 g), and other functional components (p < 0.05) in TSO, while the antioxidant activity (via DPPH, ABTS, and FRAP assays) also increased. In addition, the tocopherol content decreased significantly (758.53–729.50 mg/kg). Accelerated oxidation experiments showed that roasting (170 °C/30 min) increased the oxidative stability index (OSI) of TSO from 5.35 to 7.07 h (p < 0.05). Furthermore, roasting gradually increased the content of 5-hydroxymethylfurfural (HMF) (0–1.74 mg/kg), which indicates that the oxidative stability and the degree of the Maillard reaction increased upon roasting. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) showed that moderate roasting (130 °C/20 min) improved the chemical composition, antioxidant activity, and oxidative stability of TSO. Furthermore, this work provides a useful theoretical basis for the processing and wide application of TSO in the pharmaceutical and food industries.